Analysis of Factors Relating to Nurses' Performance in Nursing Care Documentation Based on Kopelman Theory - Natalina, Upit; Saudah, Noer; Azizah, Lilik Ma'rifatul; Sajidin, Muhammad; Maryam, Dewi; Zamroni, Asroful Hulam (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurses have an important role in determining the quality of health services, however, some nurses are still found to have less than optimal performance in documentation of nursing care due to internal and external factors. Therefore, this research aims to analyze the development of training, leadership, attitudes, competencies, motivation, work design and performance of nurses in documenting nursing care based on Kopelman's theory. Method: This research used a cross-section design with a sample of 1406 nurses at RSUD Dr. Soetomo. This research used a purposive sampling technique, namely infectious disease installation nurses with the criteria of being an executive nurse and not being on leave. Data collection using a questionnaire includes independent variables in the form of training development, leadership, attitudes, competence, motivation, and work design, and the dependent variable in the form of nurses' performance in documenting nursing care. All questionnaire instruments in this research have a correlation r value of <0.5 and a Cronbach's alpha value of 0.650. Data were analyzed using logistic regression with a p-value ≤ 0.05. Results: The research results show that there is an influence between training and development (0.028), leadership (0.004), attitude (0.026), competency (0.031), motivation (0.029), and job design (0.009) on nurse performance. Conclusion: The development of training, attitudes, competencies, motivation, and good work design has an impact on high nurse performance in documenting nursing care. The performance of nursing care documentation will be optimal with democratic leadership.